Magnesium hydrides and their phase transitions. (22nd June 2016) - Paidar, V.
Abstract: The mechanism of phase transitions in magnesium dihydrides is explored with the aim how to find the ways for lowering crystal structure stability and facilitate hydrogen desorption. After recapitulation of transition metal hydrides properties, a possible mechanism of fluorite-rutile type displacive phase transition is proposed. Highlights: Transition metal hydrides of the 3d elements are analysed. A mechanism of rutile-fluorite type displacive phase transition is proposed. It is argued that the fluorite-type structure of MgH2 is less stable. Structural stability is essential for materials to be used for hydrogen storage.